Marketing Strategy Analysis In PT Bankaltimtara Tenggarong - Suhardi Suhardi; Idham Idham (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2022)
Abstract: The purpose of this research is to see the right strategy to be applied at PT. Bankaltimtara Tenggarong based on SWOT analysis. The impact of the global economic crisis, which attacks the banking sector. that some of banks experience enough problems such as customer savings to become unsecured, resulting in public distrust of the bank for their savings guarantee. Another impact is that the amount of funds that can be collected from the public to the bank is decreasing, so that the bank finds it difficult to turn its cash flow, and various other impacts. internal sample of 63 people and external as many as 74 customers. Data that can be analyzed using theoretical basics, namely SWOT analysis to identify the strengths and weaknesses of PT. Bankaltimtara Tenggarong and identify factors of opportunities and threats that come from the external environment. Based on the SWOT analysis conducted, PT Bank Kaltimtara can obtain several marketing strategies, namely: Increasing various types of competitive banking products. a). Increase customer loyalty and expand services to remote villages. b) Increase promotion to be known to remote villages. c) Focus on BUMDes and SMEs targets. d). Implement an attractive savings interest rate strategy and low credit interest rates. Keyword : Marketing Strategic